Analisis Aplikasi E-Supreme (Electronic Stunting Prevention Mobile Education) untuk Pengendali Angka Stunting di Kabupaten Cilacap - zulfikar Yusya; Dwi Maryanti; Meydy Fauziridwan; Atika Mahmudah (Jurnal Sistem Informasi dan Teknologi Informasi, 2023)
A condition of malnutrition, lack of psychosocial stimulation and exposure to repeated infections in the first 1000 days of life, causing the size to grow abnormally from the standard deviation provisions set by WHO can be referred to as stunting or stunting. The still high prevalence of stunting in Indonesia cannot be separated from problems, namely low awareness of stunting, policies that have not yet converged in providing support for stunting prevention and problems related to communication in behavior change both at the individual, community and health service levels. So seeing the long and short term impacts related to stunting and preparing young expectant mothers as a way to reduce stunting requires the Electronic Stunting Prevention Mobile Education (e-Supreme) Application for Teenagers. The choice of using the E-Supreme application is based on several studies where the use of the application has been proven to increase knowledge, behavior and has succeeded in reducing the incidence of stunting by 1.5% and can be used as a strategy to reduce stunting[1]–[4]. It is hoped that through the E-Supreme application, there will be an increase in youth's knowledge about stunting.